Metode Pendidikan Islam dan perannya: Pembentukan karakter para pemuda - Nafi'ah, Shabrina Yudhitia Alfiatun (Maliki Interdisciplinary Journal, 2024)
Education in Indonesia is still very low, especially in the religious field. Islamic education is a carefully planned education that aims to help students develop all their potential, have a good religious spirituality, and shape their learning process to benefit themselves and their surrounding community. A method is needed to produce excellent students. A method is a set of methods or techniques used by teachers in the teaching and learning process to help students or learners achieve the goals formulated in the curriculum. In the world of education, student character development is very important. Personality development in Islam is basically based on two things: Al-Quran and Hadith. Because basically these two things are the foundation of Islam. Character itself means traits that a person always likes or is proud of, and character is always a sign of one's goodness or virtue. Islamic education has an important role in shaping the character of the younger generation. In addition, Islamic education also helps in overcoming social problems and avoiding bad behavior. This Islamic education provides a good moral, ethical, and spiritual foundation for the development of the character of the younger generation.